Sekularisasi: Salah Satu Ancaman bagi Kehidupan Beragama di Indonesia - Suwandi, Zahrany Aulia (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2024)
Secularization is defined as the process of separation between religion and state, where religion no longer has a central role in public and political life. Many people say that religion is an addiction and is very restrictive in worldly life so that it must be separated from public and political life. This article aims to conclude that secularization is a complex phenomenon with various impacts on religious life in Indonesia. This study uses qualitative research with a literature study approach. The results of the study suggest that secularization can be a threat to religious life in Indonesia for several reasons. Secularism must be seen as a constructive criticism for Indonesia. Secularism can cause moral decline, but it also encourages reflection and strengthens Pancasila as the foundation of the state. The research method used in this study uses literature studies, namely by searching for and analyzing data and sources of information related to secularism. The formulation of the problem of this study, the researcher discusses the process of secularization in Indonesia, the threat of secularization to religious life in Indonesia, and how religious people in Indonesia respond to this issue. As a result, religious communities in Indonesia need to understand secularization well and respond to it wisely in order to maintain a healthy and tolerant religious life.